Do material ao imaterial: patrimônios culturais do Brasil - Corá, Maria Amelia Jundurian (2011)
Created in 2000, the Programa Nacional do Patrimônio Imaterial (PNPI) National Program of Intangible Heritage established a new form of state action related to Brazilian intangible heritages. Executed by Instituto Nacional do Patrimônio Nacional (Iphan), the program innovates by extending its object of heritage, by proposing the registration process for intangible cultural heritage and the development of safeguarding plans to determine the actions to be undertaken. The central problem is based on the following questions: a) what were the progresses and limitations of the Programa Nacional do Patrimônio Imaterial (National Program of Intangible Heritage); b) how its establishment has impacted on the Brazilian cultural policy and the dynamics of cultural property registered as Patrimônios Culturais do Brasil (Cultural Heritage of Brazil)? Based on these questions, this research aims at understand how was the process of implementation of PNPI. The research is based on the analysis of procedures for registration and documents provided by Iphan on its website, supplemented by interviews with Iphan technicians, cultural intermediaries and holders of registered cultural property. It was observed that despite its progress, the program still needs to publicize its procedures and purposes, as well as to increase its human and financial resources to meet the demands created by the program itself. In the context of the holders of cultural property, was noticed that those who obtained record make use of the title Cultural Heritage of Brazil to achieve specific benefits such as access to social rights, the possibility of generating employment and income, partnerships, brokering with other public officials, etc. That is because the title gave greater visibility to the registered holders of cultural practices, enabling better articulation of them